Drug-Coated Balloons for the Dysfunctional Vascular Access: An Evidence-Based Road Map to Treatment and the Existing Obstacles - Kitrou, Panagiotis; Katsanos, Konstantinos; Georgopoulou, Georgia Andriana; Karnabatidis, Dimitrios (Seminars in Interventional Radiology, 2022)
An underlying stenosis within the venous limb of a hemodialysis access circuit is the main etiology for graft and fistula dysfunction as well as other symptoms such as arm, breast, and neck swelling. Treatment options for both peripheral and central venous stenoses include plain old balloon angioplasty, angioplasty with drug-coated balloons, and stenting. This article discusses the current evidence for the use of drug-coated balloon angioplasty in this patient population.
Keywords: drug-coated balloons; paclitaxel; vascular access; stenosis; angioplasty; interventional radiology